Payment source and provider type in the US healthcare system. Issue 3 (March 2015) - Benitez, Joseph; Coplan, Bettie; Dehn, Richard W.; Hooker, Roderick S.
Abstract : Abstract: Greater use of physician assistants (PAs) and nurse practitioners (NPs) to meet growing demand for healthcare in the United States is an increasingly common strategy to improve access to care and control costs. Evidence suggests that payment for services differs depending on the type of provider. This study sought to determine if the source of payment for a medical visit varies based on whether care is provided by a physician, PA, or NP. Data from the National Hospital Ambulatory Medical Care Survey (2006 through 2010) were analyzed. Physicians were proportionally more likely than NPs or PAs to provide care for medical visits compensated by private insurance or Medicare. Conversely, PAs and NPs were more likely to serve as providers of care for services with other payment sources such as Medicaid and out-of-pocket.